Hydration status in adolescent judo athletes before and after training in the heat - Rivera-Brown, A. M.; Félix-Dávila, R. A. (International Journal of Sports Physiology and Performance, 2012)
Adolescent judo athletes who train in tropical climates may be in a persistent state of dehydration because they frequently restrict fluids during daily training sessions to maintain or reduce their body weight and are not given enough opportunities to drink. Purpose: Determine the body hydration status of adolescent judo athletes before, immediately after, and 24 h after (24H) a training session and document sweat Na+ loss and symptoms of dehydration. Methods: Body mass and urine color and specific gravity (USG) were measured before, after, and 24 h after a training session in a high-heat-stress environment (29.5 ± 1.0°C; 77.7 ± 6.1% RH) in 24 adolescent athletes. Sweat sodium loss was also determined. A comparison was made between mid-pubertal (MP) and late pubertal (LP) subjects. Results: The majority of the subjects started training with a significant level of dehydration. During the training session, MP subjects lost 1.3 ± 0.8% of their pretrain- ing body mass whereas LP subjects lost 1.9 ± 0.5% (P < .05). Sweat sodium concentration was 44.5 ± 23.3 mmol/L. Fluid intake from a water fountain was minimal. Subjects reported symptoms of dehydration during the session, which in some cases persisted throughout the night and the next day. The 24H USG was 1.028 ± 0.004 and 1.027 ± 0.005 g/mL for MP and LP, respectively. Conclusions: Adolescent judo athletes arrive to practice with a fluid deficit, do not drink enough during training, and experience symptoms of dehydration, which may compromise the quality of training and general well-being.